Odpowiedzi

2010-03-10T18:11:32+01:00
A)-3x+2x-10
-x-10
-x=10 */-1
x=-10

b)2x-2=7-x
2x+x = 7 + 2
3x=9 :/3
x=3

c)10=4-2x
-2x=10-4
-2x=6 :/-2
x=-3

d)-(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3 :/-2
x=-1,5

e)2(x+1)=x
2x + 2 =x
2x-x=-2
x=-2

f)2t-(3t+1)=6
2t-3t-1=6
-t=6+1
-t=5 */-1
t=-5

g)-(4+x)=2(3-x)
-4-x=6-2x
2x-x=6+4
x=10



Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-03-10T18:12:44+01:00
A).-3x+2x=10 (?)
-x=10 * (-1)
x=10
b). 2x+x=7+2
3x=9/3
x=3
c). 2x=4-10
2x=-6/2
x=-3
d).-2x+1=4
-2x=4-1
-2x=3/ (-2)
x=-1,5
e). 2x+2=x
2x-x=-2
x=-2
f). 2t - 3t - 1 =6
-t=6+1
-t=7* (-1)
t=-7
g).-4-x=6-2x
-x+2x=6+4
x=10
2010-03-10T18:16:15+01:00
A) -3x+2x-10
-3x+2x=10
-x=10/:(-1)
x=-10

b) 2x-2=7-x
2x+x=7+2
3x=9/:3
x=3

c)10=4-2x
2x=4-10
2x=-6/:2
x=-3

d) -(2x-1)=4
-2+1=4
-2x=4-1
-2x=3/:(-2)
x=1 1/2

e)2(x+1)=x
2x+2=x
2x-x=2
x=2

f)2t-(3t+1)=6
2t-3t-1=6
2t-3t=6+1
-t=7/:(-1)
t=-7

g) -(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10